A farm‐to‐fork model to evaluate the level of polyacetylenes in processed carrots. (25th April 2013) - Tiwari, Uma; Rawson, Ashish; Valverde, Juan; Reilly, Kim; Brunton, Nigel; Cummins, Enda
Summary: Naturally occurring aliphatic C17 polyacetylene compounds [falcarinol (FaOH), falcarindiol (FaDOH) and falcarindiol‐3‐acetate (FaDOAc)] in carrots are known for their bioactivity and health benefits. This study assesses the impact of pre‐ and postharvest processes (including food processing stages) on the level of polyacetylenes and evaluates subsequent human exposure using Monte Carlo simulation techniques. The model includes data inputs from both experimental and published literature sources. The sensitivity analysis highlights the importance of cultivar selection and agronomic factors. The sensitivity analysis also showed that peeling, blanching and boiling time of carrots have a significant negative influence on the level of polyacetylenes with correlation coefficients of −0.15, −0.14 and −0.19 for FaOH, −0.47, −0.23 and −0.20 for FaDOH and −0.29, −0.26 and −0.25 for FaDOAc, respectively. The scenario analysis shows the practical application of the proposed model for industrial processing of carrots. This model could facilitate food processors in optimising critical processing factors such as peeling and cutting prior to processing of carrots.